Seeing, Doing, Writing: The Write Here Project. (12th February 2016) - Rumney, Peter; Buttress, Joy; Kuksa, Iryna
As political agendas change, the teaching of writing continues to evolve, encompassing different writing practices in an attempt to address the perceived needs for literacy in our society. This article presents the Write Here project, which aims to boost children's social development and literacy attainment through engagement with visual art, play, and multimodal learning, delivered in both art gallery and classroom settings. The valuable knowledge gained at the end of this study was evaluated and developed further through a series of extended collaborations between professional, postgraduate and undergraduate writers, and schoolchildren and their teachers. Our findings suggest that engaging young learners with creative, playful, multimodal activities will foster their confidence and motivation to engage with the subject and, more importantly, will lead to a significant improvement in literacy attainment.